2017
DOI: 10.1017/jpa.2017.64
|View full text |Cite
|
Sign up to set email alerts
|

More-complete remains ofProcolpochelys charlestonensis(Oligocene, South Carolina), an occurrence ofEuclastes(upper Eocene, South Carolina), and their bearing on Cenozoic pancheloniid sea turtle distribution and phylogeny

Abstract: Abstract.-New and more-complete material of Procolpochelys charlestonensis Weems and Sanders, 2014 provides the first detailed information on the skull, jaw, and plastron of this species, which occurs in the Oligocene Ashley and Chandler Bridge formations near Charleston, South Carolina. This material allows a much more detailed comparison of this turtle with the co-occurring pancheloniid species Ashleychelys palmeri Weems and Sanders, 2014 and Carolinochelys wilsoni Hay, 1923a, as well as with its Miocene suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…We used an updated version of the informal supertree of Foth & Joyce (2016) as the phylogenetic backbone for various statistical analyses, which differs from the published version in the position of some extinct marine turtles. In particular, pan-chelonioids were resolved according to Weems & Brown (2017) and protostegid turtles, including the 'dermochelyoids' of Bardet et al (2013) and Lapparent de Broin et al (2014), were placed as sister to thalassochelydians, as originally proposed by Joyce (2007) (but see Raselli, 2018 and for alternative phylogenetic placements for protostegids). The tree was time-calibrated in R using the package paleotree (Bapst, 2012) using information from the ages of fossils and from molecular clock studies.…”
Section: Phylogenymentioning
confidence: 86%
“…We used an updated version of the informal supertree of Foth & Joyce (2016) as the phylogenetic backbone for various statistical analyses, which differs from the published version in the position of some extinct marine turtles. In particular, pan-chelonioids were resolved according to Weems & Brown (2017) and protostegid turtles, including the 'dermochelyoids' of Bardet et al (2013) and Lapparent de Broin et al (2014), were placed as sister to thalassochelydians, as originally proposed by Joyce (2007) (but see Raselli, 2018 and for alternative phylogenetic placements for protostegids). The tree was time-calibrated in R using the package paleotree (Bapst, 2012) using information from the ages of fossils and from molecular clock studies.…”
Section: Phylogenymentioning
confidence: 86%
“…The diagram of relationships proposed by Zangerl (1953bZangerl ( , 1971Zangerl ( , 1980 was supported by the introduction of all these taxa, and of others not studied by Zangerl (1953b) and Zangerl and Turn-bull (1955), in the cladistic analysis proposed by Parham and Pyenson (2010). New works included the late Eocene Priabonian Osonachelus decorata, coded by Lapparent de Broin et al (2014b), and several North American Senonian forms coded or examined by Weems and Brown (2017) and Weems and Sanders (2014). However, Lapparent de Broin et al (2014b) reported many problems relative to the phylogenetic position of some forms.…”
Section: Comparisons and Discussionmentioning
confidence: 92%
“…Some cladistic analyses performed for Chelonioidea and Dermochelyoidea provided relevant data for the definitions and separation of subgroups (Bardet et al, 2013;Brinkman et al, 2009;Hirayama, 1995Hirayama, , 1998Hirayama and Chitoku, 1996;Joyce et al, 2004; Pérez-García and Lapparent de Broin, 2013; Lapparent de Broin et al, 2014a, b;Parham and Fastovsky, 1997;Parham and Pyenson, 2010). Only eight shell characters were coded for Eochelone brabantica in the cladistic analysis characters proposed by Parham and Pyenson (2010) (subsequently used, with few modifications, by Lapparent de Broin et al, 2014b;Weems and Brown, 2017;Weems and Sanders, 2014). Other characters coded for this taxon corresponded to elements unknown in E. voltregana n. sp.…”
Section: Comparisons and Discussionmentioning
confidence: 99%
See 2 more Smart Citations